2001
DOI: 10.1038/sj.ijo.0801649
|View full text |Cite
|
Sign up to set email alerts
|

Adipose depot-specific expression of cIAP2 in human preadipocytes and modulation of expression by serum factors and TNFα

Abstract: BACKGROUND: Visceral obesity is more closely associated with many deleterious metabolic sequelae than obesity per se. The identi®cation of properties that distinguish fat cells of the omentum from adipocytes situated elsewhere in the body may lead to the development of therapeutic strategies targeting visceral obesity. We have previously demonstrated that cIAP2 mRNA is signi®cantly overexpressed in omental (Om) compared with subcutaneous (Sc) adipocytes. This molecule is involved in the TNFa signalling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The same authors also showed that cIAP2 mRNA expression is higher in human preadipocytes from OM than that from SC fat. 15 However, their study focused only on mRNA levels. As mRNA expression does not always reflect protein expression or the concentration of the fully processed protein, we extended the observation by certifying that the principal difference between OM and SC adipose tissue occurs also on the protein level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same authors also showed that cIAP2 mRNA expression is higher in human preadipocytes from OM than that from SC fat. 15 However, their study focused only on mRNA levels. As mRNA expression does not always reflect protein expression or the concentration of the fully processed protein, we extended the observation by certifying that the principal difference between OM and SC adipose tissue occurs also on the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with human isolated adipocytes, preadipocytes cultured in serum containing medium have higher cIAP2 mRNA levels and also lower sensitivity to TNFa-induced apoptosis. 14,15,17 Therefore, the expression of cIAP2 in SC and OM adipose tissue may reflect depot-specific susceptibility to apoptosis, and thereby adipose tissue loss or deposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…differential display and reverse transcriptase-polymerase chain reaction; fat depot THERE ARE TWO TYPES OF ADIPOSE TISSUE, subcutaneous and visceral. Recent studies indicate that adipocytes in these two fat depots show differences in basal metabolic properties, for example, in regulating volume, lipid composition, and so on (22,24). There is considerable current interest in visceral adipose tissue because of its relationship with various diseases such as cardiovascular disease, type 2 diabetes mellitus, hyperlipidemia, and syndrome X.…”
mentioning
confidence: 99%
“…There are a number of potential reasons why visceral adipose tissue may contribute to abnormalities in metabolism; among these are its anatomical site and pattern of venous drainage, and the presence of intrinsic and unique features of visceral adipocytes. The venous drainage of visceral adipose tissue is via the portal system, directly providing free fatty acid as a substrate for hepatic lipoprotein metabolism and glucose production (16,22,24). Additionally, in vitro studies using labeled tracers have demonstrated that visceral adipocytes have higher rates of lipid turnover than subcutaneous adipose tissue (19,20).…”
mentioning
confidence: 99%